Tuition-free secondary education and women's attitudes toward intimate partner violence: Evidence from Sub-Saharan Africa - Pragya Bhuwania; Jody Heymann (Elsevier, 2022)
Intimate partner violence against women (IPVAW) is devastatingly common around the world. It rose further during the pandemic, increasing the urgency of finding interventions to prevent IPVAW and supporting women's ability to exit violent situations. Interventions that prevent violence and eliminate views among perpetrators that violence is acceptable should be top priority. It is also critical to study women's attitudes toward IPVAW as these shape women's responses to the abuse and their exit options. Moreover, research shows that these attitudes have a direct impact on women's health outcomes. We examine the effect of tuition-free secondary education on women's attitudes toward IPVAW across 29 Sub-Saharan African countries using data from the Demographic and Health Surveys conducted between 2000 and 2019. Using the difference-in-difference-in-differences strategy, we estimate the change in women's attitudes toward IPVAW in countries that implement tuition-free secondary policy compared with countries with tuition-free primary alone and those without any tuition-free policy during the study period. We find that while tuition-free primary education policy alone did not reduce the probability of IPVAW being perceived as justified, tuition-free secondary reduced it significantly. The probability that IPVAW was perceived as justified under at least one circumstance declined by 5.3 percentage points more on average in countries that adopted tuition-free policy up to the secondary level relative to those that adopted only up to the primary level. Tuition-free secondary affects four of the five circumstances under which IPVAW was perceived as justified - if she goes out without telling the husband, argues with him, neglects children or refuses sex. We observed no declines for when she burns food, suggesting different factors affecting this outcome. Our findings underscore the importance of making a stronger commitment toward policies that make secondary education more accessible to not only benefit education outcomes but also advance population health.